Perancangan dan Implementasi Website Dusun Wanarata Sebagai Media Informasi Desa Baturaden, Kecamatan Lubuk Raja, Kabupaten Ogan Komering Ulu - Muhammad Ripaldi; Irlin Pardede; Nadya Dwi Murti; Jasilatul Maryani; Lucyana Lucyana (Universitas Dehasen Bengkulu, 2026)
This study aims to design and implement the Wanarata Hamlet website as an information medium for the community of Baturaden Village, Lubuk Raja District, Ogan Komering Ulu Regency. The primary issue is the absence of an integrated digital medium, causing information dissemination to remain manual and ineffective. This study adopted a Research and Development method with a qualitative descriptive approach and the Waterfall system development model, consisting of needs analysis, design, implementation, testing, and evaluation stages. The system was developed using the WordPress platform supported by HTML, CSS, and JavaScript. Black Box Testing was applied to ensure that system functions met the specified requirements. The results indicate that the developed website is capable of presenting hamlet information systematically, is easily accessible, and can be independently managed by local administrators. Furthermore, the website improves the effectiveness of information delivery, transparency, and communication between the hamlet administration and the community. Therefore, the Wanarata Hamlet website serves as an effective information medium to support public services and community participation in village development.